Effects of substrate bias voltage on the phase structure, mechanical and wear resistance properties of tungsten boride films. Issue 8 (15th April 2022) - Zhao, Qiang; Wang, Jia; Gu, Xinlei; Sun, Weidong; Wang, Kaiwen; Pan, Jingjie; Zhu, Xinyi; Wen, Mao; Zhang, Kan
Abstract: Tungsten boride (WB x ) films are widely used in material protection due to their high hardness. However, the wear resistance of these films needs to be improved through enhancing their toughness while maintaining their high hardness in order to significantly extend the service life of mechanical parts. Based on the characteristics of structural diversity caused by differences in the boron (B) content in WB x, in this study, magnetron sputtering was used to deposit WB x films at different substrate bias voltages, with the aim of regulating the microstructure and further optimizing the mechanical and wear resistance properties of the films. Increasing the bias voltage helps to reduce the B content of WB x without changing the original dual-phase (WB2 and W2 B) structure. The synergetic effects of the dual-phase structure, solid solution strengthening of B atoms, and gradual increase in the compressive stress are conducive to enhancing the hardness of WB x . Meanwhile, the decrease in B content leads to an increase in the relative content of the W2 B toughening phase, improving the film toughness. For the film grown at −120 V, the dual optimization of hardness and toughness is achieved, resulting in super wear resistance in the atmosphere at an ultra-low wear rate of 5.2 × 10 − 18 m³/Nm. However, although the reduction of B content improves the metallicity and toughness, due to the disappearance of the WB2 hard phase, the hardness and wear resistance of the WB x film are weakened at bias voltages above −120 V.